Development of E-learning Module based on Multiple Representation Integrated with GeoGebra - Rizki Hananan Sari; A. Halim; Yusrizal Yusrizal (Jurnal Penelitian Pendidikan IPA, 2021)
The purpose of this research is to know the feasibility, practicality, and effectiveness of e-learning modules based on multiple representations integrated with Geogebra at students of class X semester two at Aceh Seulimuem Senior High School no 1. This study uses Research and Development Method with the ADDIE model. The result for feasibility is very feasible to use with the average validation assessment in the amount of 82.95%. At the same time, the practicality from students responses got average percentage is 87.80 % classified within the very practical criteria. The effectiveness shows from the Mann Whitney U test shows that there is a difference in the average value of pre-test and post-test participants learners, which can be summarized that the module is effective to be applied.